2020
DOI: 10.13031/trans.13903
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation Savings from Smart Irrigation Technologies and a Smartphone App on Turfgrass

Abstract: HighlightsAll tested smart irrigation technologies regulated irrigation based on real-time soil moisture and weather conditions.Treatments based on SMS, ET, or smartphone app applied less water than the comparison treatment by 51% to 63%, 28% to 66%, and 51% to 63%, respectively.The payback period for the different technologies ranged between 0 and 12 months.Abstract. A plot study comparing a variety of irrigation scheduling technologies was conducted in Gainesville, Florida, from 2015 to 2017. Our study objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
5
1
Order By: Relevance
“…In 2019, however, the NDVI and percent green cover of the Rachio treatment decreased, despite similar irrigation water applications as the B-Hyve treatment, and tracked more closely to those of the control and Skydrop treatments. This finding is in contrast to that of several other studies that found that turfgrass quality remained acceptable with the implementation of smart irrigation controllers (Cardenas et al, 2020;Davis et al, 2009;Serena et al, 2019) and suggests that the effects of smart irrigation controllers on turfgrass health and quality may vary by location and over time.…”
Section: Discussioncontrasting
confidence: 99%
“…In 2019, however, the NDVI and percent green cover of the Rachio treatment decreased, despite similar irrigation water applications as the B-Hyve treatment, and tracked more closely to those of the control and Skydrop treatments. This finding is in contrast to that of several other studies that found that turfgrass quality remained acceptable with the implementation of smart irrigation controllers (Cardenas et al, 2020;Davis et al, 2009;Serena et al, 2019) and suggests that the effects of smart irrigation controllers on turfgrass health and quality may vary by location and over time.…”
Section: Discussioncontrasting
confidence: 99%
“…Smartphone applications to make irrigation scheduling easier based on local weather data have been developed (Migliaccio et al, 2015), and these apps can result in similar irrigation savings as smart controller technologies (Cardenas et al, 2020); however, studies have shown that trying to alter behavior alone can have a limited effect over time. Haley et al (2007) showed that manually adjusting timer irrigation schedules led to 30% reduction in irrigation with no negative effect on turfgrass quality.…”
Section: Human Factormentioning
confidence: 99%
“…Irrigation for turf and landscape is a major use of municipal water in the U.S. and continues to be scrutinized by water planners and regulators looking for additional ways to conserve water. Four journal articles in this Special Collection were related to turf and landscape irrigation, three concerning irrigation controllers (Cardenas et al, 2020;Conger and Dukes, 2020;Dukes, 2020), and the other article (Allen et al, 2020b) was previously discussed in the Evapotranspiration section.…”
Section: Turf and Landscape Irrigationmentioning
confidence: 99%
“…A two-year research study in Florida with smart irrigation technologies and a smart phone application (SP) was discussed by Cardenas et al (2020). Irrigation treatments based on the advanced technologies [i.e., soil moisture sensor (SMS), estimated ET, or SP] saved approximately 30% to 65% more water than traditional time-based irrigation control.…”
Section: Turf and Landscape Irrigationmentioning
confidence: 99%
See 1 more Smart Citation